2015
DOI: 10.1007/s40846-015-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Theta Burst Cortical Electrical Stimulation for Modulating Motor Plasticity in Rats

Abstract: Various forms of cortical stimulation are capable of modulating motor cortical excitability through plasticity-like mechanisms and thus might have therapeutic potential for neurological diseases. To better understand the neural mechanism underlying the cortical neuromodulation effects and to enable translational research in rodent disease models, we developed a focused brain stimulation method using cortical electrical stimulation (CES) on the motor cortex in anesthetized rats. A specific stimulation scheme us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…A previous study demonstrated the polarity effects of tDCS on MEPs, where MEPs were evoked by electric current that was delivered through same stimulation montage as tDCS [25]. In contrast to that study using the brain-thorax montage, we used a bipolar CES, which induced current similar to that by TMS in the cortex, to evoke MEPs in the current study [15]. The CES-MEP method provided a more focal stimulation than the brain-thorax montage for targeting the motor cortex and allowed better quantitative measurements of neuromodulation in motor excitability after tDCS [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study demonstrated the polarity effects of tDCS on MEPs, where MEPs were evoked by electric current that was delivered through same stimulation montage as tDCS [25]. In contrast to that study using the brain-thorax montage, we used a bipolar CES, which induced current similar to that by TMS in the cortex, to evoke MEPs in the current study [15]. The CES-MEP method provided a more focal stimulation than the brain-thorax montage for targeting the motor cortex and allowed better quantitative measurements of neuromodulation in motor excitability after tDCS [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…All animal procedures were conducted in accordance with the guidelines of the Institutional Animal Care and Use Committee at Chang Gung University. Procedures followed for measuring motor plasticity in the rat model were similar to those described in a previous study [15].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations